Traumatic Stress Disorder Signs Diagnosing Using a Drawing - Akimova, Nataliya (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2026)
The aim of the study was to analyze the projective potential of pictorial methods in the diagnosis of acute and post-traumatic stress disorders caused by traumatic events. The study uses a theoretical methods system - analysis, synthesis, comparison, generalization, abstraction, concretization, systematization, classification - to determine the main concepts and approaches. Empirical processing of the material was carried out by using observation methods, interviews, documentation analysis, analysis of activity products and a modified projective test "Man in the Rain". The study was agreed with the the Commission on Ethics of Scientific Research of the Kherson State Agrarian and Economic University. As a result, more than 100 drawings were collected and analyzed. Based on their study, several features in the depiction of a man in the rain were identified. They are characteristics of the person with mental trauma symptoms. In general, it is emphasized that the diagnosis of PTSD requires a radically new approach and, accordingly, new diagnostic tools. In Ukraine, in conditions of war, the need for group diagnostics of PTSD is growing. Ukrainian need tools that can be used remotely, when it is not possible to wait for the end of the traumatic circumstances; when it is impossible to isolate all the traumatized in safe conditions to provide them with assistance; when mental traumas happen one by one. These methods are desirable to be able to diagnose the degree of traumatic experience and memories, avoiding excessive criticism and rationalization, overcoming repression and denial. One of the options for such diagnostics can be diagnostics using the proposed modification of the “Man in the Rain” technique. The methodology we used has shown significant projective potential, as well as a positive consultative effect in working with traumatized individuals.